IDIOMATIC POTENTIAL OF ANATOMICAL TERMINOLOGY AND ITS ROLE IN DEVELOPING ENGLISH LANGUAGE PROFICIENCY - Yu.V. Lysanets; O.M. Bieliaieva (Проблеми екології та медицини)
The article examines the idiomatic features of anatomical terminology in modern English. The authors emphasize that understanding and correct use of idiomatic expressions is an indicator of in-depth knowledge of a foreign language and an important element in preparing for international English language exams, in particular, with the aim of recognizing implicit meanings (C1 – Advanced, C2 – Proficiency levels). It has been noted that mastering idiomatic expressions constitute one of the most difficult challenges for speakers of other languages, therefore it requires additional attention during the foreign language training of students. Based on the analysis and systematization of lexicographic sources (The Oxford Dictionary of Idioms, A Dictionary of 3800 Picturesque Idiomatic Expressions, and McGraw-Hill's Dictionary of American Idioms and Phrasal Verbs), it has been shown that anatomical terminology has significant idiomatic potential and is widely reflected in the figurative language of modern English. The study has revealed 628 idioms based on 52 anatomical terms, among which the lexemes “head”, “hand”, “eye”, “heart” and “foot” have the most productive idiomatic potential, forming the core of 75, 70, 53, 46 and 43 idioms respectively. The developed corpus of anatomical idioms has been organized for meaningful and accessible use in the educational process at a medical university. Familiarizing students with English anatomical idioms in the course of ESP training contributes to the development of student's interest and motivation in learning a foreign language, broadening their outlook, and ensuring an in-depth understanding of the mechanisms of English figurative language, which is the key to successfully passing international proficiency tests and communicating in a foreign language environment.